1992
DOI: 10.4095/133546
|View full text |Cite
|
Sign up to set email alerts
|

Glacial and environmental geology of northeastern Manitoba

Abstract: Quaternary deposits in northeastern Manitoba are related to pre-Wisconsin and Wisconsin glaciations, the Sangamon Interglaciation ,and postglaciallakes and seas. During the Wisconsin Glaciation, the map area was continually glaciated by Laurentide ice from two centres of outflow. Keewatin ice flowed southward and deposited a sandy to bouldery granitic till sheet, the surface of which is divided into belts of rib moraine and crevasse fillings. A second ice mass, centred over Hudson Bay, flowed westwards and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 0 publications
1
63
0
Order By: Relevance
“…Shallow flows and slides in ice-rich colluvium are common where forest fires have altered the insulative properties of the organic mat. Dredge and Nixon (1992) suggested that low ice contents at depth were responsible for the absence of massive permafrost-related slope failures along the rivers in this area.…”
Section: Previous Workmentioning
confidence: 99%
“…Shallow flows and slides in ice-rich colluvium are common where forest fires have altered the insulative properties of the organic mat. Dredge and Nixon (1992) suggested that low ice contents at depth were responsible for the absence of massive permafrost-related slope failures along the rivers in this area.…”
Section: Previous Workmentioning
confidence: 99%
“…The growing season ranges from 100 to 143 days, and prevailing winds are from the northwest. The area is underlain by continuous permafrost (Dredge and Nixon 1992). A more detailed description of the area is reported in Dredge (1992), Dredge andNixon (1992), andBrook (2001).…”
mentioning
confidence: 99%
“…The region has a marine subarctic climate with a mean annual temperature of -7.3°C ranging from 12°C in July to -28°C in January. Precipitation averages 400 mm annually (rainfall equivalent) (Dredge and Nixon 1992). The growing season ranges from 100 to 143 days, and prevailing winds are from the northwest.…”
mentioning
confidence: 99%
See 2 more Smart Citations